A Silk Cranial Fixation System for Neurosurgery. Issue 6 (26th January 2018) - Liu, Keyin; Shi, Zhifeng; Zhang, Shaoqing; Zhou, Zhitao; Sun, Long; Xu, Tao; Zhang, Yeshun; Zhang, Guozheng; Li, Xinxin; Chen, Liang; Mao, Ying; Tao, Tiger H.
Abstract: Cranial fixation should be safe, reliable, ideally degradable, and produce no hazardous residues and no artifacts on neuroimaging. Protein‐based fixation devices offer an exciting opportunity for this application. Here, the preclinical development and in vivo efficacy verification of a silk cranial fixation system in functional models are reported by addressing key challenges toward clinical use. A comprehensive study on this fixation system in rodent and canine animal models for up to 12 months is carried out. The silk fixation system shows a superb performance on the long‐term stability of the internal structural support for cranial flap fixation and bone reconnection and has good magnetic resonance imaging compatibility, and tolerability to high dose radiotherapy, underscoring the favorable clinical application of this system for neurosurgery compared to the current gold standard. Abstract : A silk cranial fixation system for neurosurgery in long‐term animal models is reported by addressing key challenges toward clinical use, including manufacturing large‐size defect‐free silk parts, insight on structure–strength relations in bulk silk, tunable mechanical strengths and degradation rates, incorporating therapeutic agents, and compatibility with magnetic resonance imaging, X‐ray radiation, and Gamma sterilization.